Take and Eat. Creation and Disgust in mother! by Darren Aronofsky (Itinera, 2024)
In 2017, at the end of the screening for the 74th Venice International Film Festival, the audience left the cinema reacting to mother! by Darren Aronofsky with whistles and ex- pressions of outrage. The film is embedded in the members of the audience through the choice of a semi-subjective protagonist, mother, closing them inside the house from which she herself is unable to leave. Her husband, a poet in creative crisis, regulates the narra- tive. The house, the world, the womb: a pure environment intimately related to the body of the mother and her maternal function, principle and nature of everything. This symbolic and sacred order will be progressively deconstructed by an escalation of impurities and invasion: the violence induced by the human beings themselves, will cause an ineffable fall into abjection made of disturbing esoteric calls, mixtures of flesh and matter. Ever greater degrees of abomination erupt in what we realize to be an allegory of the biblical creation in its primary concept of origin, genesis of life on Earth. Relying on the analysis that Julia Kristeva makes of the semiotics of biblical abomination, we can see in mother! a mixture of blood and promise of fecundation that Aronofsky uses to reveal the evil, the tendency to murder and the death drive of humanity. These are degenerative and devour- ing elements that will culminate in infanticidal theophagy, unleashing the phantasmatic force of the mother, abused and emptied, until the total decay of a vengeful destruction. Unlike an apocalyptic cinema that hopes for a new beginning after the end of things, we are witnessing monstrous resignation – mixed with attraction and repulsion – for a limit that, once crossed, can no longer be traced. Cinema acts by forcing us to look in a mirror, revealing the disgusting animality inherent in the human.
Keywords: Apocalypse, Motherhood, Abjection, Theophagy